Effect of therapeutic ' reality validation' on the 'schizophrenic dance':a preliminary study - Cameron, Bonny Wint (University of Limpopo ( Medunsa Campus ), 2010)
The aim of this study was to determine the effect of therapeutic ‘reality validation’ on the ‘schizophrenic dance’ based on the principles of a therapy outcome study. The objective of this study was to reduce the observable degree of psychosis in the schizophrenic patient and to facilitate the patient into entering a closer relationship with the therapist through the use of a new therapeutic approach called ‘reality validation’. This was done using a qualitative, exploratory research design. The research was conducted by examining transcribed video recordings of the administered therapeutic ‘reality validation’ by a trained clinician with patients diagnosed with schizophrenia. The analysis of the video recorded data was conducted independently by three trained clinicians who were each given the recordings along with the transcriptions of the recordings. The clinicians each gave a clinical description of each the patient’s behaviour separately during the sessions according to predetermined questions which were all indicative of the effect of ‘reality validation’ and were asked to conclude whether it had resulted in a reduction in symptomatic behaviour. The analyses of the six ‘reality validation’ sessions showed promising results. Based on five of the conducted sessions, there were clear indications that with ‘reality validation’ there was a reduction in symptomatic behaviour. In three of the sessions ‘reality validation’ had been at times incorrectly conducted, impacting on the outcome of the study. In two of these three sessions reductions in symptomatic were less evident yet still clearly present. In one session ‘reality validation’ was conducted so inaccurately that it appeared to maintain or increase the patient’s symptomatic behaviour. Despite the shortcomings in this study there was evidence to suggest that therapeutic ‘reality validation’ when used accurately can be an effective intervention, resulting in a reduction in symptomatic behaviour.
Thesis ( M Med (Clinical Psychology))--University of Limpopo, 2010.
Keywords: Schizophrenia